1999
DOI: 10.1002/(sici)1097-0142(19990315)85:6<1395::aid-cncr25>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction failure in acute lymphoblastic leukemia of childhood

Abstract: BACKGROUND Although it is widely accepted that failure to achieve complete remission (CR) portends a poor prognosis in childhood acute lymphoblastic leukemia (ALL), there is variability in the precise definition of induction failure and, to the authors' knowledge, few published data exist regarding the outcome of patients who are slow to achieve CR. METHODS Between 1987–1995, 774 children with ALL were treated on 2 consecutive protocols and were evaluable to assess the time required to attain CR. The authors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 35 publications
(39 reference statements)
2
21
1
6
Order By: Relevance
“…According to a study by Silverman et al 16 , failure of induction therapy is a relatively rare event occurring in fewer than 5% of children with ALL treated with current r egimens, but in our study the failure of induction therapy was 4% which is similar.…”
Section: Discussionsupporting
confidence: 62%
“…According to a study by Silverman et al 16 , failure of induction therapy is a relatively rare event occurring in fewer than 5% of children with ALL treated with current r egimens, but in our study the failure of induction therapy was 4% which is similar.…”
Section: Discussionsupporting
confidence: 62%
“…Although the time to attain a complete remission was not of prognostic importance in at least one adult trial, 12 we found that in childhood ALL, the time to enter a complete remission had significant implications, and the difference between a complete remission in 1 month or 2 months was a matter of life or death for the majority of slow responders. 15 …”
Section: Adherence To Protocol and Mitigating Psychosocial Factorsmentioning
confidence: 99%
“…Details of therapy have been previously published, 3,4,9,10 and are summarized in Table 2. In general, each protocol consisted of five phases of therapy: investigational window, remission induction, CNS treatment, intensification, and continuation.…”
Section: Therapymentioning
confidence: 99%
“…We have previously reported the poor prognosis of patients with persistent leukemia at the end of 1 month of therapy and have altered our definition of induction failure to include such patients. 10 Others have reported on the prognostic significance of more sensitive early response measures, including marrow response after 7-14 days of multi-agent remission induction, 39 peripheral blast counts after 1 week of corticosteroids, 26 and minimal residual disease levels during and at the completion of remission induction therapy. 40,41 We are currently investigating early response and minimal residual disease measures within the context of DFCI ALL consortium protocols.…”
Section: Figurementioning
confidence: 99%